The UV/H2O2 process based on H2O2 in-situ generation for water disinfection - Zhao, Qian; Li, Nan; Liao, Chengmei; Tian, Lili; An, Jingkun; Wang, Xin (Journal of hazardous materials letters, 2021)
[Display omitted] •UV/H2O2 with in-situ produced H2O2 was more effective than UV for disinfection.•The two-electron ORR activity can be intensified by avoiding calcination of CLs.•The calcination of CLs resulted in less oxygen functional groups.•The calcination of CLs deteriorated the conductivity and ORR reaction kinetics. Till now, the unprecedented global spread of novel coronavirus disease (nCOVID-19) threatened human health, economy as well as ecosystem services gravely. An efficient disinfection technology is highly demanded. Ultraviolet (UV)/H2O2 process seems like a potential candidate, in which H2O2 is an indispensable oxidant for HO· species production. In this work, UV/H2O2, which coupled with in-situ generated H2O2, was demonstrated as an effective process for disinfection than UV, which would play a significant role in sterilization and disinfection for water treatment. In addition, we investigated the effects of catalyst layer (CL) calcination on the performance of two-electron oxygen reduction reaction (ORR) for H2O2 generation. It is found that the two-electron ORR activity can be intensified by avoiding calcination of CL, which can be mainly due to much oxygen functional groups (CO and CO) as well as higher conductivity and reaction kinetics.